2013
DOI: 10.3112/erdkunde.2013.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Amazonian Dark Earths in Bolivia? A soil study of anthropogenic ring ditches near Baures (eastern Llanos de Mojos)

Abstract: Archaeological, pedological and ethnobotanical research of the last decades brought new insights on the view on human-environment interrelations in the Amazon. In this context, we analyse possible links between Amazonian Dark Earths (Terra Preta do Índio) traditionally known from the central Amazon of Brazil and pre-Colombian Earthworks (ring ditches) in the Llanos de Mojos of Bolivia. By doing so, we also discuss the local inhabitants' perception of soils and scrutinise the importance of soil fertility. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Interestingly, in La Chonta P and Ca concentrations were only 2.6 and 1.6 times higher in ADE compared to non-ADE soils, respectively. Similar results have been found in other regions of the Bolivian Amazon (Hastik et al 2013). These smaller differences between ADE and non-ADE are likely the result of higher background soil fertility levels in the study site.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, in La Chonta P and Ca concentrations were only 2.6 and 1.6 times higher in ADE compared to non-ADE soils, respectively. Similar results have been found in other regions of the Bolivian Amazon (Hastik et al 2013). These smaller differences between ADE and non-ADE are likely the result of higher background soil fertility levels in the study site.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been found in other regions of the Bolivian Amazon (Hastik et al . ). These smaller differences between ADE and non‐ADE are likely the result of higher background soil fertility levels in the study site.…”
Section: Discussionmentioning
confidence: 97%
“…Our respondents showed little interest in increasing manioc yields and seemed more concerned in preserving a variety of landraces to satisfy their culinary traditions, thereby maintaining what they deem to be a good quality of life. Our findings match those of Hastik et al [47] who also found no preference for the use of anthropogenic soils in an Amazonian region with low land use pressure. The favoring of a soil-manioc specificity might be an important aspect in Amazonian societies that are more integrated in the market and more interested in cultivating manioc as a cash crop, showing a proclivity to select specific soils such ADE in order to improve yields as in the case of caboclos from the Madeira River [9].…”
Section: Sources Of Manioc Variability Among Communitiessupporting
confidence: 92%
“…Considering the perspectives presented for the LF imaging, we used here this approach in an attempt to assess the remarkable fertility capacities of Amazonian soil "Terra Mulata de Índio" (TMI), by imaging the soil particles ex-situ. It is known that this anthropogenic soil (i.e., Anthrosol) presents a sustained fertility in determined rims and is characterized by a high concentration of stable organic matter, phosphorus, calcium and contains the presence of potsherds (Hastik et al, 2013;Taube et al, 2013). However, there is no precise information on the PSDs of Amazonian Anthrosols.…”
Section: Introductionmentioning
confidence: 99%